Developing inquiry-based science materials : a guide for educators - Thier, Herbert D.; Daviss, Bennett (New York : Teachers College Press, 2001)
Offers advice to beginning and experienced developers on how to create inquiry-oriented learning activities for the science education of young people.
"A project of the Lawrence Hall of Science Center for Curriculum Innovation.".
Includes bibliographical references (p. 233-235) and index.
Choice.
Professional
Keywords: Inquiry (Theory of knowledge); Science -- Study and teaching -- Activity programs -- Handbooks, manuals, etc; Science -- Study and teaching -- Activity programs -- Handbooks, manuals, etc; Theory of knowledge